Murine retroviruses use at least six different receptors for entry into Mus dunni cells. - Miller, A D (1997)
Murine retroviruses have been divided into six interference groups that use different receptors for cell entry: the ecotropic, xenotropic, polytropic, amphotropic, 10A1, and Mus dunni endogenous virus groups. Some interference is observed between xenotropic and polytropic viruses and between amphotropic and 10A1 viruses, indicating some overlap in receptor specificity between these groups, but otherwise these interference groups appear completely independent. In contrast, one study found interference among many of these groups when Mus dunni wild mouse cells were examined with an immunofluorescence assay to detect infection by the challenge virus. Here we have used a more direct assay for cell entry by using pseudotyped retroviral vectors to measure interference in M. dunni cells, and we find no evidence for extensive interference between members of different murine retrovirus groups. Indeed, our results in M. dunni cells are consistent with interference results observed in other cell types and indicate that the anomalous interference results previously observed in M. dunni cells with the immunofluorescence assay were most likely due to factors other than those that affect receptor-mediated virus entry. In summary, our results show that murine retroviruses use at least six different receptors for entry into M. dunni cells.